Predominant Washback of the General Secondary English Examination on Teachers - Ameen Tayeb, Yahya; Sallehhudin Abd Aziz, Mohd; Ismail, Kemboja (International Journal of Engineering and Technology, 2018)
General Secondary English Examination (GSEE) is the highest secondary school exit test run by the Ministry of Education, Yemen. Due to the significance of the exam being the foundation of the studentsâ€™ future, teachers are only preoccupied with how to help students get high marks in this final examination to be eligible to join university. The aim of this study is to investigate the dominant wash back effect of the GSEE on Yemeni teachers who are highly engrossed by the test. The study focuses on four pedagogical dimensions namely teachersâ€™ teaching methods, content assessment, attitudes and motivation. Mixed mode approach (qualitative and quantitative methods) was applied using classroom observations, semi-structured interviews, group discussions and a questionnaire of 72 items administered to 46 English teachers. NVivo10 was used to analyse the qualitative data. SPSS/V22 was used for analysing the quantitative data in which the Cronbach's Alpha reached (.88). The results revealed that the test had a great influence on teachers (P<.001) mainly on their teaching methods. Triangulation with the qualitative analysis confirmed equivalent implications. The study contributes a clear evidence of the powerful exam washback on the factors of the language learning practices and its influence on how and what teachers teach.Â Â